Enhancing Pancasila Student Profiles: Android-Based Learning Media in the Independent Curriculum for Elementary Schools - Hadi Purwanto; Yessy Yanita Sari; Somariah Fitriani (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study focuses on the development and evaluation of Android-based learning media designed to integrate the Pancasila Student Profile into the Independent Curriculum for elementary schools. The media aims to enhance character education and support digital-era learning. A research and development (RD) approach was employed, utilizing the Four-D model, encompassing Define, Design, Develop, and Disseminate stages. Validation was conducted by media and content experts, followed by trials with fourth-grade students. Data collection included expert assessments, student feedback, and comparative analysis of learning outcomes in experimental and control classes. Validation by media experts yielded an average score of 4.7, and content experts gave an average score of 4.47, both classified as "very feasible." Student feedback also supported the media’s effectiveness, with an average score of 4.55, similarly rated as "very feasible." Experimental trials demonstrated a significant improvement in learning outcomes, with an N-gain of 0.73 (high category) for the experimental class compared to 0.28 (low category) for the control class. The findings indicate that the Android-based learning media effectively enhances students' understanding of the Pancasila Student Profile while addressing broader goals of character education. The significant improvement in learning outcomes highlights the potential of technology-based learning tools in implementing the Independent Curriculum. This study contributes to educational research by demonstrating the feasibility and effectiveness of integrating character education into technology-based learning. The media serves as a valuable resource for advancing Independent Curriculum objectives in elementary schools.